2017
DOI: 10.1016/j.jpurol.2017.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Open versus minimally invasive surgical approaches in pediatric urology: Trends in utilization and complications

Abstract: Summary Objective Minimally invasive surgery (MIS) techniques are anecdotally reported to be increasingly used, but little objective data supports this. Our objective was to assess trends in MIS utilization across various procedures in pediatric urology and to compare postoperative complication rates between MIS and open procedures. Methods We analyzed the 1998–2012 Nationwide Inpatient Sample. We identified children (<18 years old) undergoing open and MIS inpatient procedures and any in-hospital postoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…It was previously shown that increased specialization results in lower rates of complications and mortality [ 1 9 ]. While rates of overall 30-day complications following urologic surgery in children have been reported as low as 5.9%, cases involving urinary diversion and incorporation of bowel have been associated with rates as high as 27.8% [ 10 12 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was previously shown that increased specialization results in lower rates of complications and mortality [ 1 9 ]. While rates of overall 30-day complications following urologic surgery in children have been reported as low as 5.9%, cases involving urinary diversion and incorporation of bowel have been associated with rates as high as 27.8% [ 10 12 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Trends in utilization of minimally-invasive pediatric urologic surgery are an ever-growing area of interest [ 1 ]. In 2005, the American College of Surgeons (ACS) collaborated with the American Pediatric Surgical Association to develop the ACS National Surgical Quality Improvement Program Pediatrics (NSQIP Peds) [ 2 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Minimally invasive surgery such as laparoscopic surgery or RALS has consistently shown to produce improved clinical outcomes as compared to open surgery equivalents. These outcomes include fewer complications, reduced length of hospital stay, reduced need for blood transfusion, less postoperative pain, shorter convalescence period, fewer surgical site infections, and better cosmetic results (10)(11)(12).…”
Section: Robot-assisted Laparoscopic Surgerymentioning
confidence: 99%
“…Surgery is not well tolerated in elderly or comorbid patients (Turrentine et al 2006). The development of new surgical techniques or instrumentation focuses on reducing procedural complications, incisions, scarring and recovery time (Jaffray 2005;Tejwani et al 2017). Minimally invasive techniques such as laparoscopy and endoscopy achieve these goals, and are now standard procedure over open surgeries for many indications.…”
Section: Introductionmentioning
confidence: 99%